(untitled) (KULT_online, 2019)
There is even more to Martin Hennig’s Spielräume als Weltentwürfe. Kultursemiotik des Videospiels than the title might suggest at first sight. The book not only offers a plethora of methods as well as analytical approaches towards video games from the perspective of semiotics and cultural studies, but it also works with approaches from narratology, structural text analysis, literary and media studies. Furthermore, it offers a comprehensive theory of privacy in order to analyze the video game within the variety of its narrative, ludological, and social functions.